Scattering threshold for a coupled focusing nonlinear Schrödinger system. Issue 7 (3rd May 2022) - Saanouni, T.
ABSTRACT: It is the purpose of this note, to obtain a scattering versus finite time blow-up dichotomy for a mass super-critical and energy sub-critical coupled Schrödinger system.